Prospects of Big Data Industry under Mathematical and Physical Sciences System - Hong Xiong (New Frontiers in Physical Science Research Vol. 9, 2023)
Science and technology are rapidly evolving as society develops and progresses, and communication technology is particularly intriguing at this time. The information data generated by the growth of communication technologies is gradually becoming a strategic asset, that is contended by all parties. The information age is rapidly approaching us. Information is a resource in this context, and timely and effective information resources are like wealth codes just waiting to be discovered and used. Additionally, a lot of creative businesses are advancing significantly and evolving into the modern unicorns as a result of information resources. This study is based on the characteristics of the era of the information explosion and discusses the origins and applications of information while illuminating the essence of information data resources. And I hope to explain some different perspectives on the use of information and data. Big data is becoming an important information resource for the operation of the entire society.